Clinical presentation, lipid peroxidation intensity, and features of nitric oxide production in patients with erysipelas - L. I. Ratnikova; S. A. Ship (Журнал инфектологии, 2014)
65 patients with a diagnosis of erysipelas. Examination of the patients included an analysis of lipid peroxidation products (common polyene, diene conjugates, and conjugate ketodieny trieny, Schiff bases), antioxidant defense system (enzymatic activity of superoxide dismutase) and nitric oxide metabolites (nitrates and nitrites). It was established that imbalance between excess activated lipid peroxidation and inadequate functioning of antioxidant defense system was remained during the entire period of the disease. The relationships between nitric oxide and lipid peroxidation were established. It was proved the advisability of developing and introducing new, improved schemes of pathogenetic therapy of erysipelas.